Co-Movements of Lithuanian and Central European Stock Markets Across Different Time Horizons: a Wavelet Approach - Kregždė, Arvydas; Kišonaitė, Karolina (Ekonomika, 2018)
[full article and abstract in English]This paper investigates equity market risk and co-movements between the Lithuanian stock market and the Central European stock markets. We cover the equity market returns both in time and frequency domains. We focus our studies on the changes of the market risk and co-movements of the Lithuanian and the Central European markets returns during the period of 2000–2018. The wavelet analysis was applied to segregate the returns across different time horizons (frequencies). Our findings corroborate the findings from other authors, namely that crisis periods have a great impact on the interrelations of the Central European and Lithuanian markets. We discover that volatility is concentrated in the medium and long periods (medium and low frequencies) from 1 to 3,5 years for all the markets under consideration. The absolute maximum of volatility is achieved at the period of the frequencies corresponding to the period of 3 years. We found that the co-movements with Poland, the Czech Republic and Hungary are slightly lower after the announcement of the introduction of the euro in Lithuania by the European Commission. From the investment diversification point of view, the investment horizon plays a crucial role for the level of co-movements. Our conclusion is that for Lithuanian investors, diversification with Central European markets is not useful for long horizons, because of the high co-movements. The benefit of the diversification can be achieved for the investors with time horizons less than 1 year.
Keywords: market, wavelet, coherence, co-movements, wavelet power spectrum.